2021
DOI: 10.1016/j.heliyon.2021.e06897
|View full text |Cite
|
Sign up to set email alerts
|

Does economic shocks influence household's healthcare expenditure? Evidence from rural Nigeria

Abstract: Health is profoundly influenced by several factors outside the traditional realm of healthcare. This paper employed a two-step Heckman selectivity model to examine factors influencing the decision to spend on health and the effects of economic shocks on health expenditure. The results from the first stage shows that the likelihood of spending on health increased with age, education, income, and decreases if the household is living in the northern region of Nigeria and uses mosquito bed-net. The findings from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…In this study, we focused on four key factors – income and employment, wealth endowment, social capital, and safety net programs of the government/NGOs– that could play important roles in moderating household food security and dietary diversity under the COVID-19 pandemic. Studies have shown that economic shocks in the context of income decline or job loss can adversely affect household food security (Akter & Basher, 2014 ; Smith & Frankenberger, 2018 ; Rufai et al, 2021 ). Particularly, the poor and vulnerable households are the most affected (Andam et al, 2020 ; Obayelu et al, 2021 ; Ogunmodede et al, 2020 ).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…In this study, we focused on four key factors – income and employment, wealth endowment, social capital, and safety net programs of the government/NGOs– that could play important roles in moderating household food security and dietary diversity under the COVID-19 pandemic. Studies have shown that economic shocks in the context of income decline or job loss can adversely affect household food security (Akter & Basher, 2014 ; Smith & Frankenberger, 2018 ; Rufai et al, 2021 ). Particularly, the poor and vulnerable households are the most affected (Andam et al, 2020 ; Obayelu et al, 2021 ; Ogunmodede et al, 2020 ).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Household expenditure incurred is divided into food and non-food expenditures [26][27][28]. Food and nonfood expenditure are calculated using the average monthly expenditure, as presented in Table 2.…”
Section: Household Expenditurementioning
confidence: 99%
“…We adopt a livelihood approach (DFID, 1999) for our analysis, focusing on four key livelihood enhancing variables-income, wealth endowments, social capital, and government/NGOs support programs-and how the changes in these variables during COVID-19 were associated with the severity of food insecurity and dietary diversity of households. Studies have shown that economic shocks in the context of income decline can adversely affect household food security, especially for the poor (Akter and Basher, 2014;Smith et al, 2018;Rufai et al, 2021). In contrast, increases in household incomes play a significant role in access to food, promoting both adequate consumption and dietary diversity (Deaton and Deaton, 2020;Manda et al, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%